Front Cover: Theoretical and Experimental Studies on the Near‐Infrared Photoreaction Mechanism of a Silicon Phthalocyanine Photoimmunotherapy Dye: Photoinduced Hydrolysis by Radical Anion Generation (ChemPlusChem 9/2020). Issue 9 (30th July 2020) - Kobayashi, Masato; Harada, Mei; Takakura, Hideo; Ando, Kanta; Goto, Yuto; Tsuneda, Takao; Ogawa, Mikako; Taketsugu, Tetsuya
Abstract : The Front Cover shows the near‐infrared (NIR) photoreaction mechanism of IR700, a silicon phthalocyanine dye that is used in cancer photoimmunotherapy, and is attracting a great deal of attention because this treatment is less toxic to normal cells. Theoretical and experimental studies revealed that the NIR light is used only to generate the IR700 radical anion, which subsequently undergoes hydrolysis to produce hydrophobic ligand‐released dyes that initiate cancer cell death. More information can be found in the Communication by M. Kobayashi, M. Ogawa, and co‐workers (DOI: 10.1002/cplu.202000338 ).